Life cycle cost framework for smart urban faming associated with low-income community behaviour in residential neighbourhood / Puteri Sidrotul Nabihah Saarani - Saarani, Puteri Sidrotul Nabihah (2025)
Community farming, initiated by the government, aims to address food security issues among lower-income urban populations. With technological advancements, smart urban farming (SUF) has been introduced, offering technology-driven methods that yield high productivity with minimal monitoring. It also optimizes energy and space, making it highly suitable for urban environments. However, farmers face challenges such as high initial costs, difficulty in sustaining farms due to limited financial knowledge, poor management, and dependency on external support—issues often linked to the behavioral tendencies of the B40 community. These shortcomings have created a critical gap that must be addressed.